Scanning Electron Microscopic Studies on Surface Pattern of the Pollen Loads from Apis cerana in Jajarkot District - Paudayal, Khum N; Gautam, Ishan (Nepal Journal of Science and Technology, 2012)
Over nineteen species of pollen flora belonging to thirteen families were recovered from four pollen load samples from honey bee Apis cerana collected in Jajarkot district, mid-western region, Nepal. The pollen morphology was investigated using light microscopy along with scanning electron microscopy for correct identification of pollen to its lower taxonomic level and to contribute to melissopalynological studies originating from the native apiflora. The palynological assemblage identified to the generic and some up to species level belong to Alnus sp., Artemisia sp., Brassica sp., Cornus sp., Diploknema sp., Fraxinus sp., Ilex sp., Jasminum sp., Justicia sp., Ligustrum sp., Myrica esculenta, Salix sp., Strobilanthes sp., and Urtica sp. Some of the pollen grains identified to only family level, belong to, Acanthanceae, Compositae, Lamiaceae and Rosaceae. The identified pollens clearly reflect the botanical and geographical origins of the pollen load samples. Palynomorphological investigation included the description of pollen symmetry, polarity, ornamentation, aperture, shape and size. The results for the pollen assemblages and nectariferous plant sources of Jajarkot district are discussed. DOI: http://dx.doi.org/10.3126/njst.v12i0.6522 Nepal Journal of Science and Technology 12 (2011) 340-349